Charge separation in covalently bound and self-assembled donor chromophore acceptor systems - Rawls, Matthew T., author; Elliott, C. Michael, advisor; Dorhout, Peter, committee member; Meersmann, Thomas, committee member; Bailey, Travis, committee member; Fisher, Ellen R., committee member (Colorado State University. Libraries, 2007)
Donor-chromophore-acceptor (DCA) triads consisting of a central ruthenium polypyridyl complex chromophore with a covalently appended diquaternary bipyridine "diquat" acceptor and a phenothiazine donor form an interesting platform for study of fundamental photoinduced electron transfer processes. Upon photoexcitation of the chromophore, a series of electron transfer steps occurs which yields a long-lived charge separated state (CSS). Research into the electron transfer steps leading to CSS formation and decay in these triads has led to several interesting avenues for research. First, in an effort to understand why these particular triads form, upon photoexcitation, charge separated states with such high quantum efficiency (nearly unity) an important discovery arose. The quantum efficiency for charge separation appears to be dependent upon an association interaction between the donor and the chromophore ligands which holds the donor in close electronic contact with the chromophore until the donor is oxidized. To study this association, covalently bound chromophore-acceptor species have been synthesized and the photoinduced electron transfer processes with a free donor have been studied. The D/C association appears to be sufficient for the formation of CSS. Further, this self-assembled system and related studies provides conclusive evidence that high efficiency charge separation in bound triads results from this D/C association. Covalently bound donor-acceptor species were synthesized in an attempt to extend the self assembly concept to a free chromophore system. A wide variety of DA species were studied, but ultimately triad-like behavior was not observed with free chromophore systems. Though attempts were made to control solvent effects, coulombic interactions, and DA flexibility, simple self assembled triad like behavior did not arise. These complexes demonstrate a strong magnetic field effect (MFE): upon application of relatively small fields, the CSS lifetime increases by up to an order of magnitude. A model has been proposed to explain the MFE which is based on the formation of the CSS initially as a triplet. Application of a field induces Zeeman splitting of this triplet state and slows the CSS decay. DCA complexes have been synthesized with phenoxazine or phenoselenazine in place of the phenothiazine as donors. These donors provide a large variation of spin orbit coupling (SOC) of the heteroatom (O, S, Se). MFE results for these complexes with varying heteratom SOC provide some interesting details about this proposed MFE mechanism.
Missing page 58.
Keywords: analytical chemistry; chemistry; inorganic chemistry